Physical training and activity in people with diabetic peripheral neuropathy: A case report - Amelia Tirta Lestari; Dwi Rosella Komala Sari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Diabetes mellitus (DM) is the most common endocrine disorder affecting more than 100 million people worldwide, around 6% of the population. This matter characterized by hyperglycemia (high glucose levels in blood) caused by a lack or ineffective production of insulin by the pancreas which results in an increase or decrease in the concentration of glucose in the blood. Diabetic peripheral neuropathy (DPN) or what is called diabetic peripheral neuropathy is the most common complication in cases of diabetes mellitus. DPN is a disease of loss of motor, sensory and autonomic nerve function, which can affect the peripheral nervous system. Sensorimotor training is considered a technique that can improve balance. This emphasizes the function of the sensorimotor system as a unit that works to increase sensory input and motor recruitment patterns in maintaining joint stability and regulating movement through the central nervous system (CNS). Aerobic exercise is a type of physical activity that can prevent and reduce DPN. Aerobic exercise such as treadmill can train balance. Balance training shows a high positive effect on improving motor and sensory symptoms in peripheral neuropathyPurpose: To examine the effects of sensorimotor training and lower limb muscle activity in DPN patients using treadmill.Method: The research uses a case study design, namely a research method that uses various data sources that can be used as research material, describing and explaining comprehensively various aspects of an individual, group, program, organization or event systematically. Participants in this study were patients aged 64 years, female, diagnosed diabetes mellitus type 2 (T2DM) for 10 years by a doctor. This research uses an aspect identification questionnaire instrument. DPN is screened using Michigan Neuropathy Screening Instrument (MNSI). Static balance is determined by romberg test and for dynamic balance it is measured by timed up and go test. Functional lower limb muscle strength is checked using tests Five Time Sit to Stand (5xSST).Results: The data for the respondent is a housewife aged 64 years, last education is junior high school with status as a housewife. The patient suffered from T2DM for 10 years with a hemoglobin 1AC level of 6.8 mg/dl, was overweight as indicated by the patient's BMI of 26 kg/m2. Often feels pain in both legs, when the patient walks and does strenuous activities with a score of 9, and the pain decreases when resting with a score of 3. Apart from that, the patient also has vision problems with a score of 20/40, meaning the patient can only see letters. at a distance of 20 feet. Even though normally letters can be seen clearly, namely 40 feet, this visual disturbance can cause the patient's balance to be disturbed. Providing treatment for 6 weeks can significantly improve the patient's quality of life as seen from the initial WHO QoL score of 58 to 86.Conclusion: Providing treadmill training for 6 weeks carried out 3 times a week showed significant results in reducing hemoglobin levels and DPN scores in T2DM patients.